Distribution and structural-functional attributions of Erythrophleum fordii Oliver in Bac Giang Province, Vietnam - Duong Thi Thanh; Zhang Ying; Nguyen Chi Thanh; Duong Quoc Hung; Do Thi Thao (Caspian Journal of Environmental Sciences)
The research was conducted in 2022 in areas where Erythrophleum fordii Oliver naturally grows in Bac Giang Province, Vietnam. The objective was to determine the distribution and silvicultural attributes of E. fordii, including its structural features and regeneration. The study results identified that E. fordii is naturally distributed in five districts of Bac Giang Province: Luc Nam, Luc Ngan, Yen The, Son Dong, and Tan Yen. E. fordii is widely distributed at altitudes ranging from 50 to 500 m, with a prominent presence between 100 and 200 m above sea level. As the altitude increases, the occurrence of E. fordii decreases. The forest areas dominated by E. fordii exhibit rich biodiversity, particularly in primary evergreen broadleaved forests on mountain soils, with a total of 71 species. The number of species contributing to the forest structure ranges from 9 to 15, depending on the forest condition. The study also revealed that E. fordii has a high composition coefficient, followed by Burseraceae, Chestnut, Jambolan, Elaeocarpus, Engelhardtia chrysolepis Hance, among others. The natural regeneration of E. fordii is low, with an average density of 680 trees per ha and 8 trees per route. However, the regeneration quality is poor. The dominance of regenerated trees varies significantly with altitude, decreasing as the altitude elevates.